RHETORICAL STRUCTURE AND LINGUISTIC FEATURES IN INTRODUCTION PARTS OF RESEARCH IN INDONESIAN LEGAL SCIENCE JOURNAL - Muhtadin, Muhtadin; Noermanzah, N. (English Department FBS UNP, 2017)
The objective of study was to provide an overview of the structure of rhetoric and linguistic features of the introduction of Indonesian research articles, especially the field of law. This study was descriptive method. Technique of collecting data used documentation in the form of scientific journal consist of 50 article jurnal of research of Indonesian language in field of law. Technique of data analyzing of this study was step model Problem Justifying Project (PJP) to present rhetorical style of preliminary article of Artikel Jurnal Penelitian (AJP) Indonesian language of Law Science. They were seen from sentence pattern, effective sentence, direct sentence, indirect sentence, active sentence, passive sentence, equivalent compound sentences, multi-layered sentences, and paragraph forming. The results show that: 1) the structure of the rhetoric of the introduction of Indonesian study articles, especially in the field of legal science, ie with the structure of states of background knowledge, explaining the field of research, justifying research activities, and announcing research to achieve the ultimate communicative purpose; 2) linguistic features of the introduction of Indonesian language research articles, especially the field of law dominated by the active sentence and the use of the word coordinator additions.Keywords: rhetorical structure, linguistic features, introduction ofresearch journal articlesÂ STRUKTUR RETORIKA DAN FITUR LINGUISTIK BAGIAN PENDAHULUAN ARTIKEL JURNAL PENELITIAN BERBAHASA INDONESIA BIDANG ILMU HUKUMAbstrakPenelitian ini bertujuan untuk memberikan gambaran tentang struktur retorika dan fitur linguistik bagian pendahuluan artikel peneltian berbahasa Indonesia khususnya bidang ilmu hukum. Metode penelitian menggunakan metode deskriptif. Teknik pengumpulan data menggunakan teknik dokumentasi berupa jurnal ilmiah terdiri dari 50 artikel jurnal penelitian bahasa Indonesia dalam bidang ilmu hukum. Teknik analisis data menggunakan langkah model Problem Justifying Project (PJP) untuk mempresentasikan gaya retorika bagian pendahuluan Artikel Jurnal Penelitian (AJP) berbahasa Indonesia bidang ilmu hukum, dilihat dari pola kalimat, kalimat efektif, kalimat langsung, kalimat tidak langsung, kalimat aktif, kalimat pasif, kalimat majemuk setara, kalimat majemuk bertingkat, dan pembentukkan paragraf. Hasil penelitian menunjukkan bahwa: 1) struktur retorika bagian pendahuluan artikel peneltian berbahasa Indonesia khususnya bidang ilmu hukumyaitu dengan struktur menyatakan latar belakang pengetahuan, menjelaskan bidang penelitian, menjustifikasi kegiatan penelitian, dan mengumumkan penelitian untuk mencapai tujuan komunikatif utama; 2) fitur linguistik bagian pendahuluan artikel peneltian berbahasa Indonesia khususnya bidang ilmu hukum didominasi oleh kalimat aktif dan penggunaan kata penghubung koordinatif penambahan.Kata kunci:Â struktur retorika, fitur lingusitik, pendahuluan artikel jurnal penelitian